Deductibles in social health insurance systems: Findings from Germany - Christian Hagist; Inken Holldorf; Claudia Pütz (Albert-Ludwigs-Universität Freiburg, Institut für Finanzwissenschaft, 2005)
One unique feature of the German health insurance system is the possibility for certain socioeconomic groups to opt-out of the otherwise compulsory system. To determine whether rates incorporating deductibles can heighten the appeal of statutory health insurance funds (SHI funds) compared with private health insurance companies, Germany`s third largest SHI fund Techniker Krankenkasse implemented a pilot scheme involving the use of deductibles. Preliminary scientific evaluations of the pilot scheme indicate that these deductibles are compatible with the principles of solidarity in the statutory health insurance system and provide an effective means of preventing defection to private health insurance companies.
urn:nbn:de:bsz:25-opus-18455
Keywords: I11; 330; Gesetzliche Krankenversicherung; Selbstbeteiligung (Versicherung); Gesundheitsfinanzierung; Solidarität; Deutschland